Regulation of acyl CoA: Cholesterol acyl transferase (ACAT) activity by mevalonate and cholesterol in isolated rat hepatocytes during perinatal development. Issue 8 (August 1986) - Bruscalupi, G.; Devirgiliis, L. Conti; Leoni, S.; Piemonte, F.; Trentalance, A.
Abstract : Acyl CoA: cholesterol acyl transferase (ACAT) activity presents marked oscillations and differential sensitivity to the "in vitro" stimulation of the kinase-phosphatase modulatory system in the perinatal rat liver. The regulation of this enzyme activity by some modulators generally active in adulthood, such as cholesterol, lipoproteins and mevalonate, has been studied in hepatocytes isolated at different developmental stages. A lack of effect of mevalonate and a positive effort of lipoprotein cholesterol have been observed at the fetal and neonatal stages. A differential prevalence is suggested of one of the two modulatory mechanisms (phosphorylation-dephosphorylation system, or substrate effect) at each developmental stage.